THE USE OF MEDIA MUSIC VIDEO TO IMPROVE STUDENTS’ COMPETENCE IN WRITING SKILL: An Experimental Research - Rahman, Armita Sari; Amin, Bahrun; Saiful (FKIP Unismuh Makassar, 2018)
This Research Objectives was to find out whether media music video can improve students competence in writing skill. Utilizing of music video as media in learning can help students shape an active mind, curious, and independent by strengthening confidence, ability expression and creativity. To analyze the data, A Pre-Experimental design was employed. It involves at class X-2 of SMAN 7 Enrekang Kabupaten Enrekang. Data were obtained through pre-test and posttest. Data analyze by using t-test. The findings showed that there was significant difference on the students’ competence in writing skill through media music video. The students mean score of pre-test experiment class was 56.36. Then in the post-test, the mean score of experiment class was 70.24. In other words, media music video can improve students’ competence in writing skill.